Camptothecin, triptolide, and apoptosis inducer kit have differential effects on mitochondria in colorectal carcinoma cells. Issue 5 (14th April 2022) - Liskova, Veronika; Kajsik, Marek; Chovancova, Barbora; Roller, Ladislav; Krizanova, Olga
Abstract : Mitochondrial fission and fusion are required for cell survival, and several studies have shown an imbalance between fission and fusion in cancer. High levels of mitochondrial fusion are observed in drug‐resistant tumor cells, whereas mitochondrial fission may be important in sensitizing tumor cells to chemotherapy drugs. Based on current knowledge, we hypothesized that different chemotherapeutics might differentially affect mitochondrial dynamics and energy production. Thus, we selected chemotherapeutics with different mechanisms of action (camptothecin, triptolide and apoptosis inducer kit) and investigated their effect on mitochondria in colorectal carcinoma cells. We report that these chemotherapeutics decreased the activity of complex I and reduced the mitochondrial membrane potential, and also decreased the size of mitochondria in the colorectal carcinoma cell lines DLD1 and HCT‐116. Treatment with camptothecin, triptolide and/or apoptosis inducer kit results in differential effects of fission on apoptosis in these cells. Our results suggest that fission is an important process in apoptosis induced by chemotherapeutics. Abstract : Mitochondria constantly change their morphology according to the requirements of the cell. In cancer cell lines (DLD1 and HCT‐116), we observed a decrease in the size of mitochondria compared to a non‐cancer cell line EAhy926. Treatment with camptothecin, triptolide, and/or apoptosis inducer kit decreased the activity of complex I, increased reactive oxygen species, reduced mitochondrial membrane potential and induced apoptosis in cancer cells.